2000
DOI: 10.1152/ajplung.2000.279.5.l779
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants of antiproliferative activity of heparin on pulmonary artery smooth muscle cells

Abstract: In addition to its anticoagulant properties, heparin (HP), a complex polysaccharide covalently linked to a protein core, inhibits proliferation of several cell types including pulmonary artery smooth muscle cells (PASMCs). Commercial lots of HP exhibit varying degrees of antiproliferative activity on PASMCs that may due to structural differences in the lots. Fractionation of a potent antiproliferative HP preparation into high and low molecular weight components does not alter the antiproliferative effect on PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 70 publications
(62 reference statements)
2
22
1
1
Order By: Relevance
“…2 An important pathological feature of pulmonary hypertension is increased medial thickening of the pulmonary artery attributable to hypertrophy and hyperplasia of pulmonary artery SMC (PASMC). 3,4 Our previous studies have shown that antiproliferative heparins significantly inhibit pulmonary vascular remodeling induced by hypoxia in rodents [5][6][7] and PASMC proliferation in culture. 8 -10 Other investigators also have reported that heparin inhibits PASMC proliferation in vitro and in vivo.…”
mentioning
confidence: 99%
“…2 An important pathological feature of pulmonary hypertension is increased medial thickening of the pulmonary artery attributable to hypertrophy and hyperplasia of pulmonary artery SMC (PASMC). 3,4 Our previous studies have shown that antiproliferative heparins significantly inhibit pulmonary vascular remodeling induced by hypoxia in rodents [5][6][7] and PASMC proliferation in culture. 8 -10 Other investigators also have reported that heparin inhibits PASMC proliferation in vitro and in vivo.…”
mentioning
confidence: 99%
“…The potential contact between heparin and its cell surface receptor is considered a critical and initial step in these antiproliferative effects of heparin (Gupta et al 1994;Han et al 1997). In addition pharmacological effects of heparin have been considered mainly anticoagulant effects and angiogenesis through interactions with a family of polypeptide growth factor that stimulated endothelial cell proliferation (Garg et al 2000). Results of various studies demonstrated that angiogenesis by heparin may be regulated by nitric oxide (NO) and high dose heparin injection resulted in systemic hypotension by NO synthesis (Casthely et al 1990;Pu et al 2002;Prior et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore heparin is considered to accelerate intrapulmonary angiogenesis such as pulmonary vascular endothelial cells migration and pulmonary vascular bed development in neonatal period (Han et al 1997), which subsequently results in reduction of pulmonary vascular resistance required for the survival of neonates as discussed above. In some institutions, heparin has been clinically employed for this purpose and its clinical efficacy in accelerating development of pulmonary vasculature has been reported (Garg et al 2000). However its detailed features including histopathological changes of intrapulmonary vessels associated with heparin treatment has not been examined at all.…”
Section: © 2005 Tohoku University Medical Pressmentioning
confidence: 99%
“…Heparin inhibits (VSMC) growth both in vivo and in vitro (Clowes and Karnovsky, 1977; Hoover et al, 1980; Khoury and Langleben, 2000); the mechanisms responsible for the anti proliferative effects of heparin are not well known. Previous studies have shown that antiproliferative heparins significantly inhibit pulmonary vascular remodeling induced by hypoxia in rodents(Hales et al, 1983; Garg et al, 2000) and PASMC proliferation in culture (Thompson et al, 1994; Cindhuchao et al, 2003). Barzu et al (1994) have suggested that long term treatment of SMC with heparin selected SMC with low sensitivity to the growth inhibition by heparin over multiple passages.…”
Section: Introductionmentioning
confidence: 99%